Pelayanan Publik oleh Dinas Kependudukan dan Pencatatan Sipil Kota Tangerang terhadap Penyandang Disabilitas - Adellia Oktavianes; Agus Sjafari; Ima Maisaroh (Epistemik: Indonesian Journal of Social and Political Science, 2024)
The assessment of services that can bring satisfaction to the community often relies on the examination of service quality. This research specifically delves into the quality of public services for individuals with disabilities within Tangerang City's Disdukcapil. The primary objective is to ensure the realization of the rights of individuals with disabilities by receiving optimal public services, thus preventing discrimination. The study adopts the Quality-of-Service theory as proposed by Zeithaml, Parassuraman, and Berry (Pasolong 2017). Utilizing a descriptive qualitative approach, the research incorporates analysis through interviews, observations, and documentation studies. The findings reveal that, according to Zeithaml, Parassuraman, and Berry's model (Pasolong 2017) measuring public service quality, the services provided by Tangerang City's Disdukcapil for individuals with disabilities have not reached an optimal level. This assessment is based on evaluations of various dimensions of public service quality, including:i) Tangible: Facilities, infrastructure, and amenities remain inadequate, and cleanliness in the service office is yet to be addressed; ii) Reliability: Document preparation procedures lack clarity and organization within the service office; iii) Responsiveness: Employees exhibit a lack of responsiveness when dealing with visitors with disabilities and lack proficiency in sign language; iv) Empathy: Some employees still display unfriendliness when providing services.In essence, the study underscores areas where improvements are needed to enhance the quality of public services for individuals with disabilities in Tangerang City's Disdukcapil.